If it's not what You are looking for type in the equation solver your own equation and let us solve it.
9(v-9)-3v=5(9+4v)
We simplify the equation to the form, which is simple to understand
9(v-9)-3v=5(9+4v)
Reorder the terms in parentheses
+(+9v-81)-3v=5*(9+4v)
Remove unnecessary parentheses
+9v-81-3v=+5+*(+9+4v+)
Reorder the terms in parentheses
+9v-81-3v=+(+45+20v)
Remove unnecessary parentheses
+9v-81-3v=+45+20v
We move all terms containing v to the left and all other terms to the right.
+9v-3v-20v=+45+81
We simplify left and right side of the equation.
-14v=+126
We divide both sides of the equation by -14 to get v.
v=-9
| 12-(5m+5)=4+4m-15 | | (-6)(0.5)= | | 3y=2x+15 | | 3z+2z-8= | | 11p-94=71 | | 5(25)+4+3(25)-24-2y=180 | | 9x-7=13-4x | | 575-329x= | | (5)(-4)= | | 4x^2+5x=81+5x | | 2m^2-12m=11 | | 6y-11=73 | | 4g+2(-6+5g)=1-g | | 5(3-a)=3a+a+-3 | | 3x-8=9x+5 | | 3z+22=16 | | x-(c+a)=bg | | 3(3x-2)=6(x-3) | | A+B+R=180 | | -11+10=-2(m+2)-3 | | -.5(b+2)+3b=-1 | | 37+3a=3(a-6)+7 | | Y-4x=(-3) | | s+4s= | | 5x-2+3x=3d+7-4d | | -4(x+2)-60=-8 | | (2x-2)(2x+1)= | | 3-7[7-(9y-9)]=0 | | x^2+43*x=0 | | 3(y+4)-10=1 | | 8x+1.2-11x=-0.9 | | 4x+2-3x-15=18 |